PENGENDALIAN DEBIT BANJIR SUNGAI LUSI DENGAN KOLAM DETENSI DI KECAMATAN TAWANGHARJO KABUPATEN GROBOGAN - S. Reza Pradana; Arianto Nugroho; Suharyanto Suharyanto; Dwi Kurniani (Departemen Teknik Sipil, Fakultas Teknik Universitas Diponegoro, 2015)
Lusi River is one of the biggest river in Jratunseluna river area that has drainage area from Rembang Regency, Blora Regency and end at Grobogan Regency. In rainy season, the Lusi river’s flow rate tend to be large and cause flood in some areas in Grobogan, Blora dan Kudus Regency. Protecting of potential areas is necessary to avoid a great loss if flood disaster happens. The existence of a detention pond expected to reduce the flood discharge in Lusi River and can overcome the flood disaster at potential area in downstream of Lusi River’s drainage area.